0528 Insomnia as a Mechanism for Improvement in Alcohol Problems Among Young Adults. (27th May 2020) - Miller, M; Freeman, L B; Park, C J; Hall, N; Sahota, P K; McCrae, C S
Abstract: Introduction: More than half of heavy-drinking young adults report symptoms of insomnia, which have been associated with alcohol-related problems. This study examined improvement in insomnia (via Cognitive Behavioral Therapy for Insomnia; CBT-I) as a mechanism for improvement in alcohol-related problems. Methods: Fifty-six heavy-drinking young adults with insomnia (ages 18-30y) were randomized to CBT-I (n=28) or single-session sleep hygiene control (SH; n=28). Of those, 43 (77%) completed post-treatment (24 SH, 19 CBT-I) and 48 (86%) completed 1-month follow-up (25 SH, 23 CBT-I). Multiple imputation was used to estimate missing data. Treatment outcomes were assessed using multilevel models. Mediation was tested using bootstrapped confidence intervals for indirect effects in the PROCESS macro. Results: CBT-I participants reported greater decreases in insomnia severity than those in the sleep hygiene group [group X time interaction, F (2, 59)=11.29, p <.001], both post-treatment and at 1-month follow-up. Both groups decreased significantly in diary-assessed sleep quality [time, F (2, 55)=40.30, p <.001], with a marginally significant interaction in favor of the CBT-I group [ F (2, 55)=2.69, p =.08]. There were no significant group by time interactions in the prediction of actigraphy-assessed sleep variables, although again, there was a marginally significant interaction in the prediction of actigraphy-assessed sleep efficiency [ F (2, 66)=2.75, p =.07]. Both groups reported significant decreases in drinking quantity over time [time, F (2, 58=13.88, p <.001]. However, CBT-I participants reported greater decreases in alcohol-related consequences than those in the sleep hygiene group [ F (2, 67)=4.13, p =.02]. In the mediation model, CBT-I did not have a direct effect on change in alcohol-related consequences ( B =1.49, SE =1.06, 95%CI=-0.65, 3.62); however, it influenced change in 1-month alcohol-related consequences indirectly through its influence on post-treatment insomnia symptoms ( B =-1.09, SE =0.57, 95%CI=-2.30, -0.05). Conclusion: CBT-I is effective in treating insomnia among heavy-drinking young adults and may be associated with reductions in alcohol-related problems due to its impact on insomnia symptoms. Support: This work was supported by funding from the University of Missouri System Research Board Office (PI Miller). Mary Beth Miller's contribution to this project was also supported by the National Institute on Alcohol Abuse and Alcoholism [grant number K23AA026895].